Adoption of cattle and pig artificial insemination (AI) by livestock keepers in Northwest Vietnam, through an AI service providers co-operative - Marshall, Karen; Nguyen, Thinh; Lo, Thanh; Thanh, Huyen Le Thi (International Livestock Research Institute, 2024)
Son La Province in northwest Vietnam is a region with a rich cultural diversity, where ethnic minorities make up about 83% of the population. Livestock, particularly beef cattle and pig farming, is essential to the local economy and culture, providing not only a source of nutrition but also a critical foundation for livelihoods. For many smallholder farmers, livestock represents both a financial asset and a means of economic resilience, while integrating livestock into crop farming systems enhances soil fertility through manure use, supporting sustainable agriculture. Earlier studies in Son La identified low adoption of AI for cattle and pigs, including due to the lack of service providers, as a limitation to livestock production (https://cgspace.cgiar.org/handle/10568/107285). In response, Chan-Henh has been developing a model for promotion of AI, working with women and men AI service providers as well as smallholder cattle keepers. On the service provision side, veterinary workers have been trained in the technique of artificial insemination (Marshall and Huyen, 2023), undergone agri-business incubation to increase business acumen (Le et al., 2024) and formulated into a co-operative for collection action, including facilitation of access to liquid nitrogen. This was to ensure that professional AI services were available in the area, and that provision of AI services was profitable to the providers. Additionally, Chan-Henh trained women and men livestock keepers on breeds, breeding and artificial insemination, to help enhance demand (Marshall and Huyen, 2023c). This approach aimed to ensure that professional AI services were accessible in the region and financially viable for providers.